'Impending Ruin' or 'Remarkable Wealth'? The Role of Private Credit Markets in the 18th-Century Cape Colony. Issue 1 (2nd January 2018) - Fourie, Johan; Swanepoel, Christie
Abstract : Credit markets develop hand in hand with a market economy. Pre-industrial credit markets, like credit (and capital) markets today, developed in order to smooth consumption, ease trade, and enable long-term investment. Yet in the 18th-century Cape Colony, a Dutch settlement at the southern tip of Africa, commentators of the day were sceptical about what an active credit market could contribute to the economy: for them, borrowing was a sure sign of poverty. Historians have expressed the same view. We present a different picture of the Cape Colony. We use 4, 160 probate inventories, listing 12, 637 credit transactions and 12, 580 debt transactions, to show that the main reason for borrowing was long-term capital investment in land through bonds, and that a particular driver of the Colony's extensive use of credit was slave ownership. We also show that those who benefited from the Colony's thriving credit market were rich, not poor.